DILEMA AGAMA DAN PANCASILA DI RUANG PUBLIK INDONESIA - Mauluddin, Agus (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This paper aims to challenge his studies (Bonotti and Seglow, 2017; Eiedat,2017; Fenton, 2016; Kaul, 2017; Kraidy and Krikorian, 2017; Nachi, 2016), which see religion and public sphere, but minus the context of Pancasila ideology. And perfecting his study Asrori (2016) who saw religion-in this case religious education in the context of the Pancasila ideology, but minus the study of public sphere in his study. Thus, this paper seeks to synthesize the position of religion in public sphere of Indonesia which has the ideology of Pancasila, and what is the policy alternative of the religious dilemma that is "brought" into public sphere of Indonesia? By using a qualitative approach, the library research method with a review of various international and national journal articles, and book reviews, this study produces at least two important findings, namely, first, religion and the state cannot be dichotomized in the ideology of Pancasila. Freedom of expressing religiosity in the public sphere becomes an embedded principle in the ideology of the Pancasila. Its implications for religious freedom in the public sphere are absolutely regulated fairly and wisely based on the principles of Pancasila. Secondly, the State and "internal" Religion needs to synergize in building freedom of expression in the public sphere; every religion in expressing its religiosity in the public sphere needs to pay attention to universal values. That is, "language" religion expressed in public sphere must have a "universal framework" that can be accepted by other citizens